Keterlaksanaan Sekolah Berwawasan Lingkungan Terhadap Sikap Peduli Lingkungan di SMA Negeri 1 Bantul - Fairuzzabadi Amrullah; Heru Nurcahyo (Indonesian Journal of Applied Science and Technology, 2021)
Realizing an environmentally sound school is a school commitment that systematically develops programs to internalize environmental values ??into all school activities. Lack of awareness and responsibility towards the environment which results in the occurrence and damage to the environment. The government is trying to create an environmentally sound education. The purpose of this study was to determine the implementation of environmentally friendly schools in schools. The method used is an observational survey method, the research subjects used are school principals, adiwiyata team, vice principals, teachers, and students. The data collection technique used non-test techniques using interview instruments, observation and documentation, then data analysis by data triangulation. Over all the school has supported environmentally friendly school activities, and has been used in the learning process, as well as the participation of school residents, and the interest from school residents will motivate themselves so that others will do the same so that the school can achieve the goals of an environmentally friendly school. sustainable.